Blended organic hole transport material and application thereof

By using multi-component blended organic hole transport materials in quantum dot light emitting diode devices, the gradient hole transport layer is formed by using the surface energy difference of fluoropolymers, which solves the problem of unclear interfaces in traditional devices and improves the light emitting performance and lifetime of the device.

CN119894239APending Publication Date: 2025-04-25DONGGUAN VOLT-AMPOPTOELECTRONICSTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311380446.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In traditional quantum dot light emitting diode (QLED) devices, due to the similar solubility of organic materials, the interface is unclear, making it difficult to build a double hole transport layer, affecting the light emitting performance of the device.

Method used

By physically blending at least one fluoro hole transport polymer with at least one other hole transport polymer, multicomponent blended organic hole transport material is obtained. By utilizing the difference in surface energy of the material, the fluoro polymer is enriched on the surface during the film formation process, forming a hole transport layer with energy level and mobility gradient.

Benefits of technology

The structure of QLED and OLED devices is simplified, the hole injection and transmission performance of the device is improved, and the advantages of high efficiency and long life are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894239A_ABST
    Figure CN119894239A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectric materials, and discloses a multi-component blended organic hole-transport material containing a fluorinated hole-transport polymer, which is used for preparing photoelectric devices such as quantum dot light-emitting diodes and organic light-emitting diodes. The components of the blended hole transport layer comprise at least one fluorinated polymer and at least one non-fluorinated polymer. The invention firstly provides a multi-component blended organic hole transport material containing a fluorinated hole transport polymer, which is high in thermal stability and good in film-forming property, can realize longitudinal gradient distribution in a film-forming process, realizes HOMO energy level and hole mobility step, is beneficial to hole injection and transport, and can be applied to the field of hole transport. The compound can be used for preparing high-performance quantum dot light-emitting devices and organic light-emitting devices; and then providing a preparation process of the multi-component blended organic hole transport material ink containing the fluorinated hole transport polymer. The quantum dot light-emitting device and the organic light-emitting device prepared by the method have a good application effect and also have very advantages in the aspect of industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optoelectronic materials, and in particular relates to a multi-component blended organic hole transport material comprising a fluorinated hole transport polymer, and its application in optoelectronic devices such as quantum dot light emitting diodes and organic light emitting diodes. Background Art

[0002] With the continuous demand for higher power efficiency and wider color gamut, quantum dot light-emitting diodes (QLEDs) have become one of the most promising candidates for the next generation of display technology because they can produce vivid and pure colors, high efficiency and low voltage driving characteristics. In the past few decades, QLED devices have made great progress in efficiency and lifetime, especially those based on II-VI elements. In particular, QLED devices with external quantum efficiency (EQE)>20% and lifetime exceeding one million hours can be achieved through simple device structure.

[0003] Technically, type II-VI quantum dots, such as CdSe / ZnS, have relatively deep energy levels, and there is an obvious hole injection barrier between the work function of the ITO anode and the valence band of type II-VI QDs. Therefore, hole transport layers (HTLs) are crucial to the device performance of QLEDs. Previous reports have shown that inserting HTLs in the QD layer and the anode or hole injection layer can significantly enhance the luminescence performance of QLEDs. However, in traditional device structures, it is still a great challenge to construct dual HTLs due to the similar solubility of organic materials, which may lead to unclear interfaces during continuous solution deposition. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, the primary purpose of the present invention is to provide a type of multi-component blended organic hole transport material comprising a fluorinated hole transport polymer. The present invention obtains a multi-component blended organic hole transport material by physically blending at least one fluorinated hole transport polymer with at least one other hole transport polymer. This type of blended organic hole transport material is dissolved in a solvent, and during the process of being processed into a film by spin coating, inkjet printing, etc., due to the difference in the surface energy of the material, the fluorinated hole transport polymer will be enriched on the surface, thereby forming a hole transport layer material with a differential distribution of energy levels and mobility gradients, which promotes hole injection and transport. This type of multi-component blended organic hole transport material can simplify the structure of optoelectronic devices such as quantum dot light-emitting diodes and organic light-emitting diodes, and improve device performance.

[0005] Another object of the present invention is to provide a process for preparing the ink of the above-mentioned blended organic hole transport material.

[0006] Another object of the present invention is to provide the application of the above-mentioned blended organic hole transport material in optoelectronic devices, especially in quantum dot light-emitting diodes and organic light-emitting diode devices.

[0007] Another object of the present invention is to provide a method for preparing a quantum dot light-emitting diode or an organic light-emitting diode device using the above-mentioned blended organic hole transport material as a hole transport layer.

[0008] The object of the present invention is achieved by the following solutions:

[0009] A multi-component blended organic hole transport material containing a fluorinated hole transport polymer, the components of which contain at least one fluorinated hole transport polymer and at least one non-fluorinated hole transport material.

[0010] The chemical structural formula of the fluorinated hole transport polymer satisfies one of the following general formulas:

[0011]

[0012] In the formula: x and y are the molar fractions of each unit component, satisfying: 0 < x < 1, 0 < y < 1, x + y = 1; n is the number of repeating units, and n is an integer in the range of 5 to 5000;

[0013] Ar1 is an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms;

[0014] Furthermore, Ar1 is preferably at least one of the following chemical structures or structural derivatives thereof:

[0015]

[0016]

[0017] Among them, R1 is the same or different and is one of an alkyl group with 1 to 30 carbon atoms, a cycloalkyl group with 3 to 30 carbon atoms, an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms; R2 is the same or different and is one of H, D, F, CN, alkenyl, alkynyl, amino group, nitro group, acyl group, alkoxy group, carbonyl group, sulfone group, an alkyl group with 1 to 30 carbon atoms, an alkoxy group with 1 to 30 carbon atoms, a cycloalkyl group with 3 to 30 carbon atoms, an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms.

[0018] Ar2 is an organic conjugated unit containing fluorine atoms and has one of the following structures:

[0019]

[0020] R3 is the same or different and is one of a fluorine atom and a perfluoroalkyl group having 1 to 10 carbon atoms. Further, the structural formula of the fluorinated hole-transporting polymer is preferably the following structure:

[0021]

[0022]

[0023]

[0024]

[0025] The non-fluorinated hole-transporting material has the following structural formula:

[0026]

[0027] In the formula: x' and y' are the molar fractions of each unit component, satisfying: 0 < x' < 1, 0 < y' < 1, and x' + y' = 1; n is the number of repeating units, and n is an integer in the range of 5 to 5000;

[0028] Ar3 and Ar4 are relatively independent and are respectively an aromatic hydrocarbon group having 6 to 60 carbon atoms or an aromatic heterocyclic group having 3 to 60 carbon atoms;

[0029] Further, Ar3 and Ar4 are respectively preferably one or more of the following chemical structures or structural derivatives thereof:

[0030]

[0031] Among them, R4 is the same or different and is an alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 3 to 30 carbon atoms, an aromatic hydrocarbon group having 6 to 60 carbon atoms, or an aromatic heterocyclic group having 3 to 60 carbon atoms.

[0032] Preferably, the structural formula of the non-fluorinated hole-transporting material is preferably one of the following structures:

[0033]

[0034]

[0035] A class of multi-component blended organic hole-transporting materials containing fluorinated hole-transporting polymers according to the present invention includes at least one fluorinated hole-transporting polymer, the content of which is greater than 0 and less than 100% by mass fraction; and further includes at least one non-fluorinated hole-transporting polymer, the content of which is greater than 0 and less than 100% by mass fraction, and the sum of its content and the content of the fluorinated hole-transporting polymer is equal to 100%.

[0036] Preferably, the multi-component blended organic hole transport material comprising a fluorinated hole transport polymer comprises at least one fluorinated hole transport polymer and at least one non-fluorinated hole transport polymer, wherein the total mass percentage of the fluorinated hole transport polymer is 10-90%.

[0037] The ink preparation process of the multi-component blended organic hole transport material comprising a fluorinated hole transport polymer described in the present invention is as follows:

[0038] At least one fluorinated hole transport polymer and at least one non-fluorinated hole transport polymer are weighed according to a mass ratio, and the at least one fluorinated hole transport polymer and the at least one non-fluorinated hole transport polymer are blended and dissolved in an organic solvent, and stirred to dissolve to obtain a blended organic hole transport material ink.

[0039] The organic solvent comprises at least one of tetrahydrofuran, chloroform, toluene, xylene, chlorobenzene, dichlorobenzene, cyclohexanone, benzoic acid, acetic acid, methyl benzoate, octahydronaphthalene, dioxane and cyclohexylbenzene.

[0040] The temperature for stirring and dissolving is 0 to 80°C, preferably 20 to 60°C.

[0041] The above-mentioned blended organic hole transport material is used in optoelectronic devices, especially in quantum dot light emitting diodes and organic light emitting diode devices.

[0042] A quantum dot light emitting diode or organic light emitting diode device comprises an anode, a cathode and at least one organic compound layer disposed between the two electrodes, wherein the organic compound layer comprises at least one blended hole transport layer; the components of the blended hole transport layer comprise at least one fluorinated polymer and at least one non-fluorinated polymer.

[0043] Preferably, the above-mentioned quantum dot light-emitting diode (QLED) or organic light-emitting diode device (OLED), its preparation method comprises the following steps:

[0044] (1) attaching a hole injection layer on the ITO substrate by spin coating or inkjet printing;

[0045] (2) forming a hole transport layer on the hole injection layer by spin coating or inkjet printing of a blended organic hole transport material ink, and annealing to remove the solvent in the ink;

[0046] (3) preparing quantum light emitting layer (QLED) or organic light emitting layer (OLED) by spin coating or inkjet printing;

[0047] (4) Optionally, an electron injection layer is prepared on the light-emitting layer by spin coating, inkjet printing or evaporation;

[0048] (5) Finally, a cathode electrode is evaporated.

[0049] The annealing described in step (2) refers to annealing at 100 to 240° C.; the thickness of the blended hole transport layer obtained in step (2) is preferably 20 to 200 nm.

[0050] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0051] The present invention first provides a high-performance blended organic hole transport material. In addition to having the advantages of high thermal stability and good film-forming properties, the fluorinated hole transport polymer and the non-fluorinated hole transport polymer in the blended organic hole transport material have different surface energies. During the film-forming process, the fluorinated hole polymer will be enriched on the surface of the transport layer, and the non-fluorinated hole transport polymer will be correspondingly enriched at the bottom, thereby forming an energy level and mobility gradient, which is beneficial to improving the hole injection and transport performance of the device. QLED and OLED devices based on this type of multi-component blended organic hole transport layer containing fluorinated hole transport polymers show the advantages of high efficiency and long life. The QLED and OLED devices prepared by this method have good application effects and are also very advantageous in industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is the atmospheric ultraviolet photoelectric energy spectrum of the blended hole transport material obtained by doping the fluorinated polymer P5 with TFB.

[0053] Figure 2 It is a device structure diagram of devices D1 to D5.

[0054] Figure 3 This is the time-of-flight secondary ion mass spectrometer spectrum of the blended hole transport layer of P5:TFB=3:7.

[0055] Figure 4 : Current efficiency-brightness curve of devices D1 to D5. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0057] The materials involved in the following examples can all be obtained from commercial channels. If the polymers cannot be purchased from commercial channels, they can be prepared by referring to New J. Chem., 2016, 40, 402-412.

[0058] Example 1

[0059] Preparation of quantum dot light-emitting device D1 (comparative example)

[0060] The device is a hole transport layer of poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] (TFB, P41), and the preparation steps include:

[0061] a) The ITO glass substrate was cleaned with isopropanol, acetone, deionized water (4 times), and isopropanol ultrasonic cleaning for 15 minutes each, and then treated with plasma for 2 minutes;

[0062] b) On the ITO anode, a thin film of hole injection layer material (poly (3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid: PEDOT:PSS) is obtained by spin coating, with a film thickness of about 40 nm, which is the hole injection layer;

[0063] c) A thin film of hole transport layer material TFB is obtained on the hole injection layer by spin coating, with a film thickness of about 40 nm. This layer is the hole transport layer;

[0064] d) On the hole transport layer, a CdSe / ZnS (dispersed in n-octane) thin film with a thickness of about 15 nm is obtained by spin coating, which is the light-emitting layer;

[0065] e) Spin-coating a ZnO nanoparticle layer (ethanol solution) on the light-emitting layer with a thickness of 40 nm, which is the electron injection layer;

[0066] f) vacuum evaporating cathode Al (100 nm) on the electron injection layer, which is the cathode reflective electrode layer;

[0067] The molecular formula of TFB described in this embodiment is as follows:

[0068]

[0069] Example 2

[0070] Preparation of quantum dot light-emitting devices D2 to D4

[0071] The device preparation method is similar to that of device D1, except that: in step c, the fluorinated polymer P5 and TFB are mixed and dissolved in xylene, and then the mixed hole transport layer is obtained by spin coating. In the mixed hole transport layer corresponding to devices D2 to D4, the mass fraction concentration of the fluorinated polymer P5 is 10%, 30%, and 50%, respectively.

[0072] The structural formula of the fluorinated polymer P5 described in this embodiment is as follows. The polymerization method of P5 refers to the document New J. Chem., 2016, 40, 402-412.

[0073]

[0074] Figure 1 This is the atmospheric ultraviolet photoelectric energy spectrum of the blended hole transport material obtained by doping the fluorinated polymer P5 and TFB. It can be seen from the figure that adjusting the proportion of the fluorinated polymer P5 can effectively adjust the HOMO energy level of the surface layer of the blended hole transport material from -5.5eV to -6.0eV.

[0075] Example 3

[0076] Preparation of quantum dot light-emitting device D5

[0077] The device preparation method is similar to that of device D1, except that the fluorinated polymer P5 is dissolved in xylene and then the blended hole transport layer is obtained by spin coating. The blended hole transport layer corresponding to device D5 is pure fluorinated polymer P5.

[0078] Example 4

[0079] Preparation of quantum dot light-emitting device D6

[0080] The device preparation method is similar to that of device D1, except that the fluorinated polymer P6 and TFB are mixed and dissolved in xylene, and then the mixed hole transport layer is obtained by spin coating. In the mixed hole transport layer corresponding to device D6, the mass fraction concentration of the fluorinated polymer P6 is 30%.

[0081] The structural formula of the fluorinated polymer P6 described in this embodiment is as follows. The polymerization method of P6 refers to the document New J. Chem., 2016, 40, 402-412.

[0082]

[0083] Example 5

[0084] Preparation of quantum dot light-emitting device D7

[0085] The device preparation method is similar to that of device D1, except that the fluorinated polymer P9 and poly (9,9-n-dioctyl-2,7-fluorene-alt-9-isooctyl-3,6-carbazole) (PF8Cz, P42) are mixed and dissolved in xylene, and then the mixed hole transport layer is obtained by spin coating. In the mixed hole transport layer corresponding to device D7, the mass fraction concentration of the fluorinated polymer P9 is 30%.

[0086] The structural formula of the fluorinated polymer P9 and the non-fluorinated polymer P42 described in this embodiment is as follows:

[0087]

[0088] Example 6

[0089] Preparation of quantum dot light-emitting device D8

[0090] The device preparation method is similar to that of device D1, except that the fluorinated polymer P30 and P43 are mixed and dissolved in xylene, and then the mixed hole transport layer is obtained by spin coating. In the mixed hole transport layer corresponding to device D8, the mass fraction concentration of the fluorinated polymer P30 is 50%.

[0091] The structural formula of the fluorinated polymer P30 and the non-fluorinated polymer P43 described in this embodiment is as follows:

[0092]

[0093] Example 7

[0094] Preparation of quantum dot light-emitting device D9

[0095] The device preparation method is similar to that of device D1, except that the fluorinated polymers P3, P29 and P41 are mixed and dissolved in xylene, and then the mixed hole transport layer is obtained by spin coating. In the mixed hole transport layer corresponding to device D9, the mass fraction concentration of fluorinated polymers P3 and P29 is 20%.

[0096] The structural formulas of the fluorinated polymers P3 and P29 and the non-fluorinated polymer P41 described in this embodiment are as follows:

[0097]

[0098] Example 8

[0099] Preparation of organic light-emitting device D10

[0100] The device is a cross-linked TFB (P44) hole transport layer, and the preparation steps include:

[0101] a) The ITO glass substrate was cleaned with isopropanol, acetone, deionized water (4 times), and isopropanol ultrasonic cleaning for 15 minutes each, and then treated with plasma for 2 minutes;

[0102] b) On the ITO anode, a thin film of hole injection layer material (poly (3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid: PEDOT:PSS) is obtained by spin coating, with a film thickness of about 40 nm, which is the hole injection layer;

[0103] c) Spin-coating the hole transport material ink on the hole injection layer, and heating and annealing at 200° C. for 30 minutes in an inert atmosphere to obtain a thin film of the hole transport layer material cross-linked TFB with a thickness of about 20 nm. This layer is the hole transport layer;

[0104] d) Spin-coating a xylene solution (1 wt.%) of blue light emitting poly (9,9-dioctylfluorenyl-2,7-diyl) (PFO) on the hole transport layer with a film thickness of about 60 nm, which is the light emitting layer;

[0105] e) Ba is evaporated on the light-emitting layer with a thickness of 0.5 nm. This layer is the electron injection layer;

[0106] f) vacuum evaporating cathode Al (100 nm) on the electron injection layer, which is the cathode reflective electrode layer;

[0107] The molecular formula of the cross-linked TFB (P44) described in this example is as follows:

[0108]

[0109] Example 9

[0110] Preparation of organic light-emitting device D11

[0111] The device preparation method is similar to that of device D10, except that the fluorinated polymer P39 and the non-fluorinated polymers P44 and P45 are mixed and dissolved in xylene, and then the mixed hole transport layer is obtained by spin coating. In the mixed hole transport layer corresponding to device D11, the mass fraction concentration of non-fluorinated polymers P44 and P45 is 30%.

[0112] The structural formulas of the fluorinated polymer P39 and the non-fluorinated polymers P44 and P45 described in this embodiment are as follows:

[0113]

[0114] The characteristic test results of the light emitting devices made in the above embodiments are shown in Table 1, Table 2, Figure 3 , Figure 4 .

[0115] Figure 2 It is a device structure diagram of devices D1 to D5.

[0116] Figure 3 The TOF-SIMS spectrum of the blended hole transport layer of P5:TFB=3:7, with the boundary of each layer defined as the intersection time of the F- / SO3- and SO3- / InO- curves. Through geometric calculations, the depth distribution of P5 can be estimated from the fluoride ion distribution. The actual content of P5 on the top surface is calculated to be about 70wt%, which gradually decreases to ~20wt% along the thickness direction, indicating that this type of fluorinated polymer hole transport material can achieve a vertical concentration gradient distribution.

[0117] Figure 4The current efficiency-brightness curves of devices D1 to D5 indicate that devices D2 to D4 using a blended hole transport material containing a fluorinated polymer have higher device performance.

[0118] Table 1 Performance parameters of quantum dot light-emitting devices

[0119] Electroluminescent Devices Luminous efficiency (cd / A) Color coordinates D1 14.08 (0.68,0.32) D2 16.02 (0.68,0.32) D3 23.13 (0.68,0.32) D4 20.11 (0.68,0.32) D5 19.87 (0.68,0.32) D6 22.78 (0.68,0.31) D7 23.55 (0.68,0.31) D8 19.58 (0.67,0.32) D9 21.87 (0.68,0.32)

[0120] Table 2 Performance parameters of organic light-emitting devices

[0121] Electroluminescent Devices Luminous efficiency (cd / A) Color coordinates D10 2.00 (0.16,0.12) D11 4.89 (0.16,0.12)

[0122] The results in Table 1 and Table 2 show that the multi-component blended organic hole transport material containing fluorinated hole transport polymers of the present invention is applied to the hole transport layer of quantum dot light-emitting devices and organic light-emitting devices, which can promote hole injection and transport by realizing energy level gradient. Compared with the devices D1, D5 and D10 with non-mixed hole transport layers, the devices based on the multi-component blended organic hole transport material containing fluorinated hole transport polymers all show higher device performance.

[0123] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A multi-component blended organic hole transport material comprising a fluorinated hole transport polymer, characterized in that It contains at least one fluorinated hole-transporting polymer in its components, and its content is greater than 0 and less than 100% by mass fraction; and it contains at least one non-fluorinated hole-transporting material, and its content is greater than 0 and less than 100% by mass fraction, and the sum of the contents of at least one fluorinated hole-transporting polymer and at least one non-fluorinated hole-transporting material is equal to 100%.

2. The multi-component blended organic hole-transporting material containing a fluorinated hole-transporting polymer according to claim 1, characterized in that: The chemical structural formula of the fluorinated hole-transporting polymer satisfies the following general formula: In the formula: x and y are the molar fractions of each unit component, satisfying: 0 < x < 1, 0 < y < 1, x + y = 1; n is the number of repeating units, and n is an integer in the range of 5 to 5000; Ar1 is an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms; Ar2 is an organic conjugated unit containing a fluorine atom; The non-fluorinated hole-transporting material has the following structural formula: In the formula: x' and y' are the molar fractions of each unit component, satisfying: 0 < x' < 1, 0 < y' < 1, x' + y' = 1; n is the number of repeating units, and n is an integer in the range of 5 to 5000; Ar3 and Ar4 are relatively independent and are respectively an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms.

3. The multi-component blended organic hole-transporting material containing a fluorinated hole-transporting polymer according to claim 2, characterized in that: Ar1 is at least one of the following chemical structures or derivatives of the following structures: Among them, R1 is the same or different and is one of an alkyl group with 1 to 30 carbon atoms, a cycloalkyl group with 3 to 30 carbon atoms, an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms; R2 is the same or different and is one of H, D, F, CN, alkenyl, alkynyl, amino group, nitro group, acyl group, alkoxy group, carbonyl group, sulfone group, an alkyl group with 1 to 30 carbon atoms, an alkoxy group with 1 to 30 carbon atoms, a cycloalkyl group with 3 to 30 carbon atoms, an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms; Ar2 is an organic conjugated unit containing a fluorine atom and has one of the following structures: R3 is the same or different and is one of a fluorine atom and a perfluorinated alkyl group with 1 to 10 carbon atoms; Ar3 and Ar4 are relatively independent and are respectively more than one of the following chemical structures or derivatives of the following structures: Among them, R4 is the same or different and is an alkyl group with 1 to 30 carbon atoms, a cycloalkyl group with 3 to 30 carbon atoms, an aromatic hydrocarbon group with 6 to 60 carbon atoms or an aromatic heterocyclic group with 3 to 60 carbon atoms.

4. The multi-component blended organic hole-transporting material containing a fluorinated hole-transporting polymer according to claim 1, characterized in that: The structural formula of the fluorinated hole-transporting polymer is selected from the following structures: Among them, n is an integer in the range of 5 to 5000; The structural formula of the non-fluorinated hole-transporting material is selected from the following structures: Among them, n is an integer in the range of 5 to 5000.

5. The multi-component blended organic hole-transporting material containing a fluorinated hole-transporting polymer according to claim 1, characterized in that: The total mass fraction of the at least one fluorinated hole-transporting polymer is 10 - 90%.

6. Use of the multi-component blended organic hole transport material comprising a fluorinated hole transport polymer according to any one of claims 1 to 5 in optoelectronic devices, especially in quantum dot light emitting diodes and organic light emitting diode devices.

7. A quantum dot light emitting diode or organic light emitting diode device, characterized in that The invention comprises an anode, a cathode and at least one organic compound layer disposed between the two electrodes, wherein the organic compound layer comprises at least one layer of a multi-component blended organic hole transport material comprising a fluorinated hole transport polymer as claimed in any one of claims 1 to 5.

8. The quantum dot light emitting diode or organic light emitting diode device according to claim 7, characterized in that The preparation method comprises the following steps: (1) attaching a hole injection layer on the ITO substrate by spin coating or inkjet printing; (2) applying the ink of the multi-component blended organic hole transport material comprising a fluorinated hole transport polymer as claimed in any one of claims 1 to 5 on the hole injection layer to form a hole transport layer by spin coating or inkjet printing, and annealing to remove the solvent in the ink; (3) preparing a quantum light emitting layer or an organic light emitting layer by spin coating or inkjet printing; (4) Optionally, an electron injection layer is prepared on the light-emitting layer by spin coating, inkjet printing or evaporation; (5) Finally, a cathode electrode is evaporated.

9. The quantum dot light emitting diode or organic light emitting diode device according to claim 8, characterized in that: The preparation process of the ink of multi-component blended organic hole transport material containing fluorinated hole transport polymer comprises the following steps: At least one fluorinated hole transport polymer and at least one non-fluorinated hole transport polymer are weighed separately, and the at least one fluorinated hole transport polymer and the at least one non-fluorinated hole transport polymer are blended and dissolved in an organic solvent, and stirred to dissolve to obtain a blended organic hole transport material ink.

10. The quantum dot light emitting diode or organic light emitting diode device according to claim 9, characterized in that: The organic solvent comprises at least one of tetrahydrofuran, chloroform, toluene, xylene, chlorobenzene, dichlorobenzene, cyclohexanone, benzoic acid, acetic acid, methyl benzoate, octahydronaphthalene, dioxane and cyclohexylbenzene.